Toxoplasma gondii infection in sentinel and free-range chickens from Argentina - Moré, Gastón Andrés (2012)
This study aimed at isolating and genotyping Toxoplasma gondii from serologically positivefree-range chickens from Argentina, and to evaluate the use of sentinel animals during ashort time period of exposure to determine environmental contamination with T. gondiioocysts. Two groups of chickens on six farms were compared in this study: (i) young, 2?3month-old broiler-type chickens reared as sentinel animals on the farms and (ii) adultchickens reared on the same farms for more than one year. Seroconversion rates of 7.0% or5.7% were observed in sentinel broiler chickens reared for a period of 74 days (January?April2010) or 88 days (August?November 2010) respectively, as shown by a T. gondii specificimmunofluorescent antibody test. Fifty-three percent(17 of 32) of adult chickens were positive and showed higher titres than sentinel animals. Isolation of T. gondiifrom tissues (brainand heart) of serologically positive chickens was achieved from six of seven free-range adultbirds with IFAT titres of 200 and higher. The isolated parasites were analysed by multi-locuspolymerase chain reaction?restriction fragmentlength polymorphism (PCR-RFLP). The isolated T. gondii showed three different genotypes: two genotypes consisted in atypical allelecombinations, and the remaining genotype had exclusively clonal type II alleles. All isolates obtained at a single farm, corresponded to the same genotype. The T. gondii genotypesobserved are identical to those described in cats, dogs, chickens and capybaras elsewherein South America. Two isolates, which showed different allele combinations in PCR-RFLP,were characterized in a mouse virulence assay. While one isolate showed a low virulencea second isolate was of intermediate virulence to mice.